2020
DOI: 10.20944/preprints202005.0057.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Hydroxychloroquine Is Associated with an Increase of Survival in COVID-19 Patients: An Observational Study

Abstract: Background: There is no treatment proven effective against COVID-19. Several drugs with in vitro potential against SARS-CoV-2 virus have been proposed. Hydroxychloroquine has in vitro anti-viral and immunomodulatory activity, but there is no current clinical evidence of its effectiveness changing the outcome of the disease. Methods: We enrolled all 18-85 years old inpatients from Central Defense Hospital “Gómez Ulla”, Madrid, Spain, who were hospitalised for COVID-19 and had a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…One of these studies, however, reported results comparing the use of HCQ with that of another antiviral agent, lopinavir/ritonavir (LPV/r) [94] . The two observational studies conducted with the same dosage preceded by a LD resulted in opposite results, with the trial using the higher LD (800 mg/day) reporting positive results [99] . Among the studies using 600 mg of HCQ daily, four reported positive outcomes and three did not.…”
Section: Human Clinical Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…One of these studies, however, reported results comparing the use of HCQ with that of another antiviral agent, lopinavir/ritonavir (LPV/r) [94] . The two observational studies conducted with the same dosage preceded by a LD resulted in opposite results, with the trial using the higher LD (800 mg/day) reporting positive results [99] . Among the studies using 600 mg of HCQ daily, four reported positive outcomes and three did not.…”
Section: Human Clinical Studiesmentioning
confidence: 98%
“…The results of a number of clinical trials and observational studies [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] have been reported so far, many of which present methodological limitations due to conditions of duress of an unexpected pandemic ( Table 1 ). Two studies also suffer from poor reporting, with no dosage being declared [ 88 , 95 ] and one of them including in the HCQ arm patients with worse baseline characteristics than the control group [88] .…”
Section: Human Clinical Studiesmentioning
confidence: 99%
“…Novales et al reported decreased mortality in patients treated with HCQ (27 out of 123, 22%) compared to the control arm (21 out of 43, 48.8%) in a retrospective analysis in patients admitted with COVID-19. Besides small sample size, lack of blinding and retrospective study method, other limitations of this study included use of other antiviral and anti-inflammatory medications, younger patients in the HCQ arm (61.5 years vs 68.7 years), and cause of mortality not specified [64]. A large retrospective population wide analysis of patients with confirmed/ suspected COVID-19 from Portugal compared the incidence of PCR positivity in those who were already on HCQ to those who were not [65].…”
Section: Studies Suggesting Hcq Efficacy In Covid-19mentioning
confidence: 99%
“…7 A recently published observational study with a cohort of 166 patients, hospitalized due to COVID-19, showed increased mean survival by 1.4 to 1.8 times. 8 However, better evidence from an adequately powered randomized control trial is still not available.…”
Section: A Saudi Family With Sickle Cell Disease Presented With Acutementioning
confidence: 99%